2015
DOI: 10.1186/s12987-015-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cigarette smoke extract and hyperglycemic conditions on blood–brain barrier endothelial cells

Abstract: BackgroundDiabetes and tobacco smoking are significant public health concerns which have been shown to independently impact the blood–brain barrier (BBB). Since smoking is a risk factor for diabetes and shares some of the common pathological pathways leading to metabolic abnormalities, it is hypothesized that their combination would produce additive or synergistic BBB dysfunction. Therefore, the objective of this study was to assess this hypothesis and evaluate the magnitude of these effects in vitro using hCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 59 publications
8
67
0
Order By: Relevance
“…Activation of oxidative/ inflammatory stress signaling cascades by drugs of abuse is the primary mechanism for increased endothelial activation and leukocyte migration across the BBB into the brain. Recent studies from our group (Sajja et al, 46 Naik et al, 115 and Prasad et al 146 ) and other groups (Alfieri et al 147 and Sandberg et al…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 65%
“…Activation of oxidative/ inflammatory stress signaling cascades by drugs of abuse is the primary mechanism for increased endothelial activation and leukocyte migration across the BBB into the brain. Recent studies from our group (Sajja et al, 46 Naik et al, 115 and Prasad et al 146 ) and other groups (Alfieri et al 147 and Sandberg et al…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 65%
“…Similarly, Hawkins and coworkers confirmed that nicotine down regulated the expression of the ZO-1 tight junction protein in the BBB, the follow-on of increased permeability [53]. Furthermore, many other scientific communities revealed that nicotine alters the function of the BBB Na +À K +À 2Cl À co transporter through mediation of a7nAChR [54][55][56].…”
Section: Dysfunction Of the Blood-brain Barriermentioning
confidence: 84%
“…Further, we and others have found that TS promotes glucose intolerance and increases the risk of developing type-2 diabetes mellitus ( 2DM ) [27], [28] with which it shares other pathogenic traits including the high risk of cerebrovascular and neurological disorders like stroke [29] via ROS generation, inflammation, and blood-brain barrier ( BBB ) impairment [30], [31], [32]. Recent findings [33], [34] from our group, supports an additive release pattern of angiogenic, oxidative and inflammatory factors by BBB endothelial cells in response to hyperglycemia ( HG ) and/or stroke conditions with comcomitant exposure to cigarette smoke extracts ( CSE ), thus suggesting the involvement of common pathogenic modulators of BBB impairment. To this end, Metformin ( MF ; a widely prescribed, firstline anti-diabetic drug) before and after stroke injury has been shown to reduce stress and inhibit the inflammatory responses [34], [35].…”
Section: Introductionmentioning
confidence: 99%